Barilla SpA(A) Harvard Business Case Study: A short Reaction Paper on Supply Chain Implementation Challenges - Siddiqui, Atiq (2020)
A short reaction paper on supply chain implementation challenges in context of famous Barilla SpA(A) Harvard Business Case Study. Various other reading are also included in the paper.